Management Information Systems and their evolution towards the Fourth Industrial Revolution (National Administration Journal, 2022)
The following article is research about Management Information Systems in evolutionary process towards the fourth industrial revolution; the problem to solve is: How to quickly face all strategic decisions within an environment full of data that might not be a real information? To do this, a current bibliographic review has been prepared to develop the hypothesis about artificial intelligence does not replace the human intelligence, instead of it, complements and facilitates the quality people’s life due to the technology’s advantages and the reduction in low value-added activities.
Keywords: Information; globalization; technology; intelligence